Interdependence between the aerobic degradation of BPA and readily biodegradable substrates by activated sludge in semi-continuous reactors - Ferro Orozco, Ana Micaela (2018)
The objective of the present work was to analyze the interrelationship between the aerobic degradation of BPA and readily biodegradable substrates by activated sludge (AS) in semi-continuous reactors (SCRs). AS were obtained from three SCRs fed with glucose, acetate or peptone. AS from these reactors were used as inocula for three SCRs that were fed with each biogenic substrate, and for three SCRs that were fed with the biogenic substrate and BPA. In all cases, dissolved organic carbon (DOC), BPA, total suspended solids (TSS) and respirometric measurements were performed. Although BPA could be removed in the presence of all the tested substrates, AS grown on acetate exhibited the longest acclimation to BPA. Reactors fed with peptone attained the lowest TSS concentration; however, these AS had the highest specific BPA degradation rate. Specific DOC removal rates and respirometric measurements demonstrated that the presence of BPA had a negligible effect on the removal of the tested substrates. A mathematical model was developed to represent the evolution of TSS and DOC in the SCRs as a function of the operation cycle. Results suggest that the main effect of BPA on AS was to increase the generation of microbial soluble products. This work helps to understand the relationship between the biodegradation of BPA and readily biodegradable substrates.